2010
DOI: 10.1111/j.1469-7998.2010.00760.x
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of body form and metamorphosis: insights from the crested newts

Abstract: Exploring the pattern of size and shape changes during the ontogeny of closely related species is of fundamental importance because it provides an insight into the processes that lead to the evolutionary diversification of body forms and into understanding the adaptations and constraints during growth and development. In this study, we explored the interspecific variation of body size and shape changes during postembryonic development (from the mid-larval period up to the end of metamorphosis) of four crested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 32 publications
4
24
0
Order By: Relevance
“…However, while general trends appear relatively uniform, allometric trajectories frequently vary among closely related species (LArSon, 2005;IvAnovIć et al, 2007IvAnovIć et al, , 2008, providing a potentially important mechanism of morphological differentiation, both in extant and extinct taxa (wITzMAnn et al, 2009). The same is true for body shape variation before and through metamorphosis in newts (vAn BUSkIrk, 2009;IvAnovIć et al, 2011), although further studies should investigate the generality of the results obtained for Triturus, since remarkable variation of allometric patterns has been observed in some cases (vAn Figure 3: yearly evolution of the number of publications using GM methods to analyse morphological variation in extant and extinct amphibians and reptiles. Data retrieved from Google Scholar and Isi web of Science.…”
Section: Allometric Patterns: Shape Change Due To Sizementioning
confidence: 97%
See 1 more Smart Citation
“…However, while general trends appear relatively uniform, allometric trajectories frequently vary among closely related species (LArSon, 2005;IvAnovIć et al, 2007IvAnovIć et al, , 2008, providing a potentially important mechanism of morphological differentiation, both in extant and extinct taxa (wITzMAnn et al, 2009). The same is true for body shape variation before and through metamorphosis in newts (vAn BUSkIrk, 2009;IvAnovIć et al, 2011), although further studies should investigate the generality of the results obtained for Triturus, since remarkable variation of allometric patterns has been observed in some cases (vAn Figure 3: yearly evolution of the number of publications using GM methods to analyse morphological variation in extant and extinct amphibians and reptiles. Data retrieved from Google Scholar and Isi web of Science.…”
Section: Allometric Patterns: Shape Change Due To Sizementioning
confidence: 97%
“…Most studies investigating allometric relationships, both in an ontogenetic and static context of allometry (i.e. GoULD, 1966), indicate that large part of the shape variation observed is attributable to sizeshape allometry (see MonTEIro & ABE, 1997;BIrcH, 1999;BonnAn, 2007;SMITH & coLLyEr, 2008;pIrAS et al, 2010;cHIArI & cLAUDE, 2011;IvAnovIć et al, 2011 for illustrative examples from different groups). caution is advised to avoid conceptual misunderstandings: while GM methods remove size variation through GpA or similar superimposition procedures, the allometric dependence of shape on size still remains in the data and can be investigated (MonTEIro, 1999).…”
Section: Allometric Patterns: Shape Change Due To Sizementioning
confidence: 99%
“…Empirical studies have shown that evolutionary modifications of ontogeny can reduce as well as increase disparity (e.g., Zelditch et al 2003a;Adams and Nistri 2010;Drake 2011;Frédérich and Vandewalle 2011;Gerber 2011;Ivanović et al 2011;Piras et al 2011;Urošević et al 2013). Although it may seem intuitively obvious that developmental constraints should limit disparity, low disparity can even result from the lack of developmental constraints because, in the absence of constraints restricting modifications of ontogeny, two or more modifications of ontogeny can counteract each other; a phenomenon termed "counterbalancing" (Zelditch et al 2003a) or "ontogenetic convergence" (Adams and Nistri 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The most dynamic patterns of disparity may result from complex life-cycles because the decoupling of between phases can allow each one to adapt independently (e.g., Strauss and Altig 1992;Fisher-Rousseau et al 2010;Frédérich and Vandewalle 2011;Ivanović et al 2011). In effect, this decoupling makes developmental stages modular in that each stage can respond selection without interfering with the adaptations of another phase.…”
Section: Introductionmentioning
confidence: 99%
“…To capture larval shape, both landmarks and semilandmarks presenting the shape of dorsal caudal fin at larvae and tail shape were used [20]. We applied a procedure for mapping the geometric morphometric data onto a known phylogeny [2123].…”
Section: Figurementioning
confidence: 99%